2020
DOI: 10.1016/j.xphs.2019.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function Assessment and High-Throughput Quantification of Site-Specific Aspartate Isomerization in Monoclonal Antibody Using a Novel Analytical Tool Kit

Abstract: Isomerization of surface-exposed aspartic acid (Asp) in the complementarity-determining regions of therapeutic proteins could potentially impact their target binding affinity because of the sensitive location, and often requires complex analytical tactics to understand its effect on structure-function and stability. Inaccurate quantitation of Asp-isomerized variants, especially the succinimide intermediate, presents major challenge in understanding Asp degradation kinetics, its stability, and consequently esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…To develop a QC-compliant workflow capable of both rapid serotype AAV identification and PTM characterization, it is important to understand the PTMs present on the AAV VPs. PTMs on biotherapeutic proteins are monitored as potential CQAs to inform process development, batch consistency, product stability, and more, as their presence can influence product quality, efficacy, and potentially patient safety. , Comprehensive PTM analysis is crucial for in-depth characterization of full-length AAV VPs, as it aids in the proper identification of different VP proteoforms present and any potential consequences their presence might cause. For PTM determination, peptide mapping and relative PTM quantitation of AAV2 using on-bead pepsin digestion and nano-LC separation were performed in parallel to full-length VP analysis, following the procedure described by Guapo et al One hundred percent sequence coverage was obtained after filtering identified peptides in BPF as described in the section describing AAV peptide mapping data processing for improved peptide mapping confidence (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…To develop a QC-compliant workflow capable of both rapid serotype AAV identification and PTM characterization, it is important to understand the PTMs present on the AAV VPs. PTMs on biotherapeutic proteins are monitored as potential CQAs to inform process development, batch consistency, product stability, and more, as their presence can influence product quality, efficacy, and potentially patient safety. , Comprehensive PTM analysis is crucial for in-depth characterization of full-length AAV VPs, as it aids in the proper identification of different VP proteoforms present and any potential consequences their presence might cause. For PTM determination, peptide mapping and relative PTM quantitation of AAV2 using on-bead pepsin digestion and nano-LC separation were performed in parallel to full-length VP analysis, following the procedure described by Guapo et al One hundred percent sequence coverage was obtained after filtering identified peptides in BPF as described in the section describing AAV peptide mapping data processing for improved peptide mapping confidence (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, any alteration or heterogeneity induced by PTMs in mAb CDRs, such as asparagine deamidation and aspartate isomerization, pose a risk of loss of antibody efficacy. 64 , 65 Where such risks were present in mAb CDRs, PTM mitigating mutations were introduced. PTM mitigated humanized mAbs retained equivalent affinity to fentanyl and carfentanil by BLI ( Table 1 ), and they maintained optimal biophysical characteristics ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Deamidation rates can be predicted based on the amino acid sequence and three-dimensional structure of the protein. In the case of IFNA2a, the extent of deamidation varies in the order Asn45 > Asn156 > Asn93 > Asn65 . In addition, the present study has not examined the effect of asparagine to isoaspartic acid mutation (Figure a) …”
Section: Discussionmentioning
confidence: 99%
“…69 In addition, the present study has not examined the effect of asparagine to isoaspartic acid mutation (Figure 1a). 80 In Summary, we used high-resolution 2D NMR methods to determine how asparagine deamidation affects the structure, stability, aggregation, and function of interferon alpha-2a, and we compared these with our recent results on the effect of methionine oxidation. 23 Identifying the local structural changes helped us in understanding how these two common chemical modifications are similar or different in terms of their effect on the aggregation and function of IFNA2a.…”
Section: Structural Analysis Of the Effect Of Asparagine Deamidation ...mentioning
confidence: 99%